2012
DOI: 10.1096/fj.12-218503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spaceflight and ground recovery on mesenteric artery and vein constrictor properties in mice

Abstract: Following exposure to microgravity, there is a reduced ability of astronauts to augment peripheral vascular resistance, often resulting in orthostatic hypotension. The purpose of this study was to test the hypothesis that mesenteric arteries and veins will exhibit diminished vasoconstrictor responses after spaceflight. Mesenteric arteries and veins from female mice flown on the Space Transportation System (STS)-131 (n=11), STS-133 (n=6), and STS-135 (n=3) shuttle missions and respective ground-based control mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 65 publications
(114 reference statements)
5
27
0
Order By: Relevance
“…Therefore, the aim of the present study was to test the effect of an 8-day HU on the Ca 2+ signaling toolkit of the VSMC in MCA from HU rats. Our results strongly suggest that the level of RyR expression plays a crucial role in the adaptation of VSMC from animals exposed to gravity modulation [4,12].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, the aim of the present study was to test the effect of an 8-day HU on the Ca 2+ signaling toolkit of the VSMC in MCA from HU rats. Our results strongly suggest that the level of RyR expression plays a crucial role in the adaptation of VSMC from animals exposed to gravity modulation [4,12].…”
Section: Discussionsupporting
confidence: 59%
“…In the same time a decrease of RyR2 expression was found in mesenteric arteries and veins [4]. In these cases, the modification of the Ca 2+ signal only depended on the decreases in RyR1/2 expressions (without modification in VDCC-induced signals) and this was correlated with a decrease of contraction and the suspected decrease of blood loading induced by HU or μG.…”
Section: Role Of Ryr In Hu and Microgravitymentioning
confidence: 78%
“…During the last 15-min period, the vasodilator sodium nitroprusside (10 −4 M) was added to the vessel chamber to ensure complete relaxation of the vascular smooth muscle. Maximal intraluminal diameter and medial wall thickness were first determined at the end of this second 15-min incubation using videomicroscopic techniques [2931]. Maximal intraluminal diameter and medial wall thickness were taken as the mean of three separate measurements from positions randomly selected along the PNA length.…”
Section: Methodsmentioning
confidence: 99%
“…of the upper body region, whereas there are atrophic adaptations and reduced contractile responsiveness in arteries of the lower body region (Tuday et al 2007;Lin et al 2009;Zhang et al 2012;Behnke et al 2013;Taylor et al 2013). For the large and elastic conduit arteries, it is reported that simulated microgravity induced an increase in blood pressure and flow in the common carotid artery of rats (Zhang 2013).…”
Section: Vascular Remodeling During Real/simulated Microgravitymentioning
confidence: 99%
“…Studies of astronauts have indicated that altered autoregulation of cerebral vasculature and the inability to adequately elevate peripheral vascular resistance may be the fundamental causes for the occurrence of orthostatic intolerance after spaceflight (Blaber et al 2011;Behnke et al 2013;Taylor et al 2013). In the past few decades, ground-based animal studies using a tail-suspended hindlimb unweighted (HU) rat model have revealed that simulated-microgravity-induced arterial remodeling is different for large elastic arteries, medium-and small-sized arteries, and arterioles in different anatomic regions (Zhang 2001(Zhang , 2013.…”
Section: Introductionmentioning
confidence: 99%